STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGUATKAN KARAKTER RELIGIUS PESERTA DIDIK MELALUI KEGIATAN KEAGAMAAN DI MTS NURUL HUDA BANJARSARI - Mufidatul Fitria, Irfan Musadat (JIPI (Jurnal Ilmiah Pendidikan Islam), 2026)
This ponder points to depict the devout character of understudies at MTs Nurul Huda Banjarsari and investigate the techniques executed by Islamic Devout Instruction (PAI) instructors in cultivating and fortifying devout character through different devout exercises. In expansion, this ponder moreover recognizes components that back or ruin the execution of these methodologies. The strategy utilized could be a case consider with a subjective approach, whereas information is collected through perception, interviews, and documentation. The comes about of the ponder demonstrate that students' devout character is still not in agreement with desires. Hence, PAI instructors execute techniques through a arrangement of organized devout exercises that are carried out routinely, such as congregational supplication, recitation of the Qur'an, Islamic thinks about, social exercises with devout subtleties, and commemoration of Islamic occasions. These exercises are aiming to instill devout values ​​and fortify students' devout character. In expansion, the victory of this technique is additionally upheld by a conducive school environment and the interest of students' guardians.